Extraction of Rutin from the Leaf of Male Carica papaya Linn. using Microwave-Assisted and Ultrasound-Assisted Extractive Methods - See Khai Chew; When Hui Teoh; Sok Lai Hong; Rozita Yusoff (ASEAN Journal of Chemical Engineering, 2022)
The extraction yield of rutin from the male Carica papaya Linn leaf using Microwave-Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE) methods were investigated and compared. Extraction parameters were analyzed to determine the effects on the yield of rutin. The efficiencies of both extractive methods were also compared. In MAE, the effect and square effect of ethanol mixture concentration, along with its interaction effect with the solid-liquid (S/L) ratio, was found to have significantly influenced the rutin yield. The square effect of particle size was also determined to be important in MAE. In UAE, the effect and square effect of ethanol mixture concentration was found to be crucial to the yield of rutin. The square effect and its interaction effect with extraction time were noticeably significant in UAE. A higher optimized yield of rutin (4.06 ± 0.2 mg/g) was obtained using UAE at an ethanol mixture concentration of 51.5%, sonication time of 70.5 min, the particle size of 355 µm, and S/L ratio of 1:108.6 wt/wt papaya leaf/ethanol mixture despite having longer extraction time and higher energy requirement per gram of rutin than MAE. In contrast, MAE was found to be more efficient by having a higher yield obtained per hour of extraction (27.38 g/h), lower energy consumption (10 W/h), and lower energy required per gram of ruin (3.65 W.h/g). In terms of a greener extraction technique, MAE would be a better fit by consuming lesser extraction solvent and energy to extract rutin from papaya leaf.